A practically simple, catalyst free and scalable synthesis of N-substituted ureas in water. Issue 38 (13th June 2018) - Tiwari, Lata; Kumar, Varun; Kumar, Bhuvesh; Mahajan, Dinesh
Abstract : A wide range of amines can be converted to N -substituted ureas using KOCN and aq. HCl without heating, organic solvent or catalyst. Abstract : A practically simple, mild and efficient method is developed for the synthesis of N -substituted ureas by nucleophilic addition of amines to potassium isocyanate in water without organic co-solvent. Using this methodology, a variety of N -substituted ureas (mono-, di- and cyclic-) were synthesized in good to excellent yields with high chemical purity by applying simple filtration or routine extraction procedures avoiding silica gel purification. The developed methodology was also found to be suitable for gram scale synthesis of molecules having commercial application in large volumes. The identified reaction conditions were found to promote a unique substrate selectivity from a mixture of two amines.